(untitled) (Asian Journal of Pharmaceutics (AJP), 2023)
The oral route technique is the most common technique for the oral administration of drugs into the body. It overcomes that the problems like drug targeting to organs can cause problems for administration through the oral route. The ideal solution to solve the issues of the quick release and brief gastrointestinal residence of liquids is to design a unique strategy, which is an in situ drug delivery system. It also prolongs the gastric residence time and controls the rate of drug release which can improve oral bioavailability and reduce the frequency of dosing. It is a particular variety of hydrogel that can hold a significant quantity of water and biological fluids without swelling. In in situ gelling systems, polymers such as guar gum, gellan gum, xanthan gum, carrageenan, xyloglucan, pectin, chitosan, and thiolate chitosan are used. The gel produced by the in situ gelling technique is thinner than the duration of gastric retention. The main aim of this review is to focus on the in situ gel principle, classification, advantages, disadvantages, and its application as a floating in situ gel system.